Diagenetic regimes in Arctic Ocean sediments: Implications for sediment geochemistry and core correlation. (1st September 2016) - Meinhardt, A.-K.; März, C.; Schuth, S.; Lettmann, K.A.; Schnetger, B.; Wolff, J.-O.; Brumsack, H.-J.
Abstract: Dark brown sediment layers are a potential stratigraphic tool in Quaternary Arctic Ocean sediments. They are rich in Mn, Fe, and trace metals scavenged from the water column and were most likely deposited during interglacial intervals. In this study, we combine sediment and pore water data from sediment cores taken in different parts of the Arctic Ocean to investigate the influence of early diagenetic processes on sediment geochemistry. In most studied cores, Mn, Co, and Mo are released into the pore waters from Mn oxide dissolution in deeper (>1.5 m) sediment layers. The relationship between sedimentary Mn, Co, and Mo contents in excess of the lithogenic background (elementxs ) shows that Coxs /Moxs values are a diagnostic tool to distinguish between layers with diagenetic metal addition from the pore waters (Coxs /Moxs  < 1), layers affected by Mn oxide dissolution and metal release (Coxs /Moxs  > 10), and unaffected layers (Coxs /Moxs from 1 to 10). Steady-state calculations based on current pore water profiles reveal that in the studied cores, the diagenetic addition of these metals from the pore water pool alone is not sufficient to produce the sedimentary metal enrichments. However, it seems evident that dissolution of Mn oxides in the Mn reduction zone can permanently alter the primary geochemical signature of the dark brown layers. Therefore, pore water data and Coxs /Moxs values should be considered before core correlation when this correlation is solely based on Mn contents and dark sediment color. In contrast to the mostly non-lithogenic origin of Mn in the dark brown layers, sedimentary Fe consists of a large lithogenic (80%) and a small non-lithogenic fraction (20%). Our pore water data show that diagenetic Fe remobilization is not currently occurring in the sediment. The dominant Fe sources are coastal erosion and river input. Budget calculations show that Fe seems to be trapped in the modern Arctic Ocean and accumulates in shelf and basin sediments. The Fe isotopic signal δ 56 Fe of the solid phase is positive (∼0.2–0.3‰) in samples defined as the lithogenic background without significant Fe enrichments. With increasing non-lithogenic Fe contents in the sediment, δ 56 Fe becomes more negative, which indicates a shelf-to-basin export of an isotopically lighter Fe fraction. We assume that the same transport process is true for Mn.